Public Trust and Regulatory Compliance - Ambar Widaningrum (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
Several studies have proven that public trust in government improves the level of policy or regulation acceptance and reduce administrative costs. In contexts where trust in government is high, citizens tend to be more willing to voluntarily comply with public policies. This article aims to explore issues of trust and distrust toward government, seen from the aspect of public compliance, both to rules or policies. The level of public trust toward government is expressed by giving its support through its conduct which complies with the existing rules. This study employed a case study research design, which was conducted in Yogyakarta, July 2015 – March 2016. It assessed the government regulation on Traffic and Road Transport and Local Regulation on Street Vendors Management. This study concludes that a number of non-compliant behaviors is a form of low publictrust in government. Disobedience is a representation of government failure to enforce the rule of law which resulted in some of the processes and procedures of public services that have not been followed by people. Level of public trust in the government regulation is an output of a variety of interrelated elements: the performance of the implemented regulation to solve public problems; consistency in the regulation’s enforcement and fairness, and government officials’ behavior, demonstrated through exemplary attitude.